2019
DOI: 10.1016/j.cjtee.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tibial nail length and olecrenon to 5th metacarpal head measurement: An anthropometric study

Abstract: PurposeDuring fracture fixation, the size of tibial nail is a vital factor affecting the outcomes and thus preoperative estimation of tibial nail length is very important. This study aims to find out whether “olecranon to 5th metacarpal head” (O-MH) measurement can be used to reliably predict the tibial nail length.MethodsThis was a cross sectional study involving 100 volunteers. Measurements were done and recorded by two observers on two separate occasions. Tibial nail length estimation measurement was done f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…On regression analysis, they showed age, gender and BMI have no statistically significant bearings on these parameters. 10 This study has shown wide limits of agreement using OMD as a predictor for nail length.…”
Section: Discussionmentioning
confidence: 71%
“…On regression analysis, they showed age, gender and BMI have no statistically significant bearings on these parameters. 10 This study has shown wide limits of agreement using OMD as a predictor for nail length.…”
Section: Discussionmentioning
confidence: 71%
“…However, due to the reasons such as obesity, density of subcutaneous fatty tissue, the presence of wounds and lesions on landmarks, fracture of the contralateral tibia, and inability to perform appropriate measurements due to edema of crus pushed orthopedic surgeons to search for landmarks from other parts of the body. 6,12 For these reasons, the OM, in which bone landmarks are easily determined, was used. Studies using these AM in the literature have obtained variable results in calculating the possible NL.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are studies in the literature with anthropometric methods [ 4 , 14 , 15 ] such as measuring the distance between the olecranon-fifth metacarpal head or with different measurement methods such as measuring the opposite extremity on radiography [ 3 , 9 , 10 ], there are limited studies evaluating the actual length of nails used with ideal length. Moreover, it is possible to come across studies that do not recommend the use of this anthropometric measurement due to its very low accuracy (51%) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%